2011
DOI: 10.1080/10402004.2011.606957
|View full text |Cite
|
Sign up to set email alerts
|

Thrust Bump Air Foil Bearings with Variable Axial Load: Theoretical Predictions and Experiments

Abstract: Thrust air foil bearings are critical components in highefficiency turbomachinery, such as two-stage compressors subjected to large and irregular axial forces. In this article, a model of thrust bump foil bearings that predicts deflection with variable axial load is developed assuming no tilting effect of the thrust collar. To predict the air clearance, deflection of the elastic foundation was used in the air film height equation. Combined Dirichlet and Neumann-type boundary conditions were used for static loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…A numerical algorithm is developed to solve equation (1) along with equation (2) to obtain the pressure in the bearing film zone, and simulations are performed with the input data taken from Lee et al 13 work shown in Table 1. The numerically obtained load data for various cases of bearing dimension as shown in Table 1 has been tabulated in Table 2.…”
Section: Validation Of Solutionsmentioning
confidence: 99%
“…A numerical algorithm is developed to solve equation (1) along with equation (2) to obtain the pressure in the bearing film zone, and simulations are performed with the input data taken from Lee et al 13 work shown in Table 1. The numerically obtained load data for various cases of bearing dimension as shown in Table 1 has been tabulated in Table 2.…”
Section: Validation Of Solutionsmentioning
confidence: 99%
“…Three types of bearings with different outer radii had been were tested to verify the theoretical model. Nevertheless, this paper didn't research the influence of the taper inlet height on bearing characteristics [25]. In 2015, Andres and Ryu etc.…”
Section: Introductionmentioning
confidence: 98%
“…In some literatures, the models considering foil deformation had been also proposed [5,[22][23][24][25][26]. In 2008, Park D. J. and Kim C. H. etc.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments emphasized the conclusion that the loadcarrying capacity of foil thrust bearings increase nonlinearly with speed and thermal runaway causes the bearing load capacity to drop off at high rotation speeds. Further, Lee et al 23 successfully developed a thrust test facility to determine the relation between load capacity and the deflection of the ''first generation'' foil thrust bearing. The nonlinear stiffness coefficients obtained with simple tests were applied to the theoretical analysis of the bearing in order to consider the nonlinear effects of the thrust bump structure.…”
Section: Introductionmentioning
confidence: 99%